PERSPEKTIF MASKULINITAS TENTANG BUNDO KANDUANG SEBAGAI BENTUK MARGINALISASI KAUM LAKI-LAKI MINANGKABAU DI SUMATERA BARAT - Putra, Bayu Sandika; Zuryani, Nazrina; Kebayantini, Ni Luh Nyoman (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT This research aims to know and analyze the marginalization of the Minangkabau males caused by the Bundo Kanduang as well as analyzing it with the perspective of the Raewyn Connell masculinity. Minangkabau Community Kinship system that matrilinal, women get a different position if compared with women in patrilineal society is the tribe of children according to the mother tribe, Pusako high down from Mamak ka kampuppies, Pusako clan Descended from the father of Kapado son and home of the house destined for women and not for men. Some of the things that caused the loss of influence and power of men in Minangkabau which also causes the male Minangkabau to be marginalized. Keywords: Analysis of masculinity perspectives, Bundo Kanduang, marginalization, Minangkabau